Factors that affect the intention to purchase branded counterfeit products among students in UiTM Kampus Bandaraya Melaka / Syahirah Maimunah Hashim - Hashim, Syahirah Maimunah (Faculty of Business and Management, 2019)
The present study seeks to examine Factors That Affect the Intention to Purchase Branded Counterfeit Products among Students in Uitm Kampus Bandaraya Melaka. The independent variables consist of four factors including brand image, social influence, price and status consumption. Meanwhile the dependent variable of this study is the intention of UiTM Kampus Bandaraya students to purchase branded counterfeit product. A total of 294 usable questionnaires was keyed in and analyzed by using SPSS software version 22. Furthermore, this research has used non-probability, convenience sampling to obtain accurate data from targeted respondents. All the data were collected for the purpose to create analysis of descriptive, correlation and regression analysis. In this study, findings show that all independent variables have a significant relationship towards intention to purchase branded counterfeit product which are brand image, social influence, price and status consumption. From this we see, the finding is useful for manufacturer or company, government, consumers and another researcher.